Pengaruh Pajak dan Tunneling Incentive Terhadap Keputusan Perusahaan untuk Melakukan Transfer Pricing dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Hilwa Sopiatul Aprila; Wulandari Cahyani Putri (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study aims to obtain empirical evidence regarding the influence of taxes, and tunneling incentives on the company’s decision to do so transfer pricing with company size as a moderation variable. This type of research is quantitative associative. The population in this study is non-cylicle consumer companies listed on the Indonesia Stock Exchange (IDX) in 2018-2023. The sampling technique uses a purposive sampling technique with certain criteria. The number of samples in this study is 21 companies listed on the Indonesia Stock Exchange (IDX) in 2018-2023. The data technique uses a panel data regression test with the help of eviews 13. The results of the study show that simultaneously taxes and tunneling incentives have an effect on transfer pricing. Taxes have no effect on transfer pricing. Tunneling incentives have a significant effect on transfer pricing. In addition, the results of the study also show that the size of the company is not able to moderate the influence of taxes on transfer pricing. Company size moderate tunneling incentives for transfer pricing.